A Glimpse Of The Earliest Forms Of Malaya’s Religious Administration In The Preindependence Period: Sir Ibrahim’s Masonic Affiliation And His Endorsement Towards Johor’s Islamic Advancement - Mohd 'Azmi Mohd Razif (Universiti Sains Islam Malaysia, 2024)
Abqari vol. 4, 2014